PENGARUH PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN DI PT MILAN ECOWOOD INDONESIA - Agung Tri Putranto (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
This study aims to determine the partial and simultaneous influence of PT Milan Ecowood Indonesia in purchasing decisions. This research is associative with a qualitative approach. The population in this study were all customers of PT Milan Ecowood Indonesia. The number of samples is 100 respondents. Data collection techniques used observation, questionnaires, literature study and documentation. The analysis technique used in this research is validity test, reliability test, normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, multiple linear regression test, correlation coefficient test, determination test, and significant test (f test and t test). The results showed that partially promotion had a positive and significant effect on purchasing decisions, this was evidenced by the simple regression value Y = 19.143 + 0.525X1, meaning that if the promotion was increased by one unit it would increase the purchase decision by 0.525 units. The value of Square is 33.2%, and the value of promotion t count is 6.979>t table 1.984 with a significant 0.000 <0.05. Partially service quality has a positive and significant effect on purchasing decisions, this is evidenced by the simple regression value Y = 15.073 + 0.627X2, meaning that if the service quality is increased by one unit, it will increase the purchase decision by 0.627 units. The value of R Square is 38.5%, the value of the promotion t count is 7.832> t table 1.984 with a significant 0.000 <0.05. Simultaneously promotion and service quality have a positive and significant effect on purchasing decisions, this is evidenced by the simple regression value Y = 10.455 + 0.308X1 + 0.441X2, meaning that if the promotion is increased by one unit it will increase the purchase decision by 0.308 units and if the service quality is improved amounting to one unit it will increase the purchase decision by 0.441 units. The value of R Square is 46.5%, and the value of F is calculated as 42.211>Ftable 2,700 with a significant 0.000 <0.05.